1991
DOI: 10.1099/00221287-137-1-107
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a derivative of Tn917 containing an outward-directed promoter and its use in Bacillus subtilis

Abstract: Engineered variants of the transposon Tn917 have been widely used to obtain insertion mutations and transcriptional fusions in Bacillus subtilis and other Gram-positive bacteria. We have developed a novel Tn917-based methodology useful for isolation and characterization of mutants resulting from gene over-expression. A Tn917 variant was constructed which contains a strong out-facing promoter near one end, able to promote transcription of genes in the vicinity of its insertion target. This transposon, designate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Transposon insertions most commonly result in null loss-of-function mutations in the gene into which they have inserted. We set out to build a transposon which, when integrated, would cause the high-level expression of the adjacent gene(s) for use in artificial-expression "gene-trap" screens (33). To build transposons with an outwardoriented, strong, constitutive promoter, the P hyspank promoter was PCR amplified using primers 1886/2271 and pDR111 as the DNA template (3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transposon insertions most commonly result in null loss-of-function mutations in the gene into which they have inserted. We set out to build a transposon which, when integrated, would cause the high-level expression of the adjacent gene(s) for use in artificial-expression "gene-trap" screens (33). To build transposons with an outwardoriented, strong, constitutive promoter, the P hyspank promoter was PCR amplified using primers 1886/2271 and pDR111 as the DNA template (3).…”
Section: Resultsmentioning
confidence: 99%
“…As proof of principle, we generated transposons with kanamycin, spectinomycin, and chloramphenicol resistance cassettes. We further generated a transposon called TnHyJump with an outward-facing, unregulated, high-expression promoter (P hyspank ) and a transposon called TnLacJump, with a promoterless lacZ gene for generating random ␤-galactosidase transcriptional reporters (24,33). The system presented here expands the kind of genetic screens that can be conducted with mariner in terms of antibiotic resistance cassettes, reporters, and many other constructs for use not only in B. subtilis but all mariner-compatible bacteria.…”
mentioning
confidence: 99%
“…GM982, a sacY-overexpressing GM904 derivative, was obtained by replacing the 1-kilobase-pair Sal I-Sst I segment containing the 5' end of sacX (3) in the GM904 chromosome with the aphA' cassette, a kanamycin-resistance gene devoid of transcription terminator (11); this substitution created an Abbreviation: RAT, ribonucleic antiterminator. *To whom reprint requests should be addressed.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of genes homologous to those encoding maltodextrin transporters suggested that oligosaccharide products resulting from the activity of an extracellular enzyme were being imported as substrates for the intracellular ␤-galactosidases. An example of this gene arrangement is found in Bacillus subtilis surrounding lacA (BSU34130) (12,14), one of two nonadjacent GHF 42-encoding genes (the other being yesZ [BSU07080] [70]). We therefore used B. subtilis as a model to explore our hypothesized function.…”
Section: -Linked Galactosidic Substrate O-nitrophenyl-␤-d-galactopyramentioning
confidence: 99%